[RETRACTION] : PEMANFAATAN APLIKASI PLAYSTORE UNTUK PRAKTIKUM PENGUKURAN DASAR PADA MATA KULIAH FISIKA DASAR 1 - . .; . . (Jurnal Pendidikan Fisika, 2022)
This article was withdrawn based on a request from the author and consideration of the JPF editorial team that there had been a double submission.